Patent engineering : a guide to building a valuable patent portfolio and controlling the marketplace - Rimai, Don (Hoboken, New Jersey : Wiley-Scrivener, 2016)
"Patents are a vital asset in the modern business world. They allow patent holders to introduce new products in to a market while deterring other market players from simply copying innovative features without making comparable investments in research and development. In years past, a few patents may have provided adequate protection. That is no longer the case. In today's world, it is critical that innovative companies protect the features of their products that give them a competitive advantage with a family or portfolio of patents that are strategically generated to protect the market position of the patent holder. A patent portfolio that deters competitors from introducing competitive products in a timely manner can be worth billions of dollars. Anything less than this is an expensive and possibly fatal distraction. This book provides a strategic framework for cost efficient engineering of patent portfolios that protect your investments in research and development and that extend the market advantages that these investments provide."--
An Introduction to Patent Engineering -- Patents and Patent Strategies? : What They Are and Why You Need Them -- Developing a Patent Strategy and Patent Engineering -- Implementing Patent Strategies and the Application Process through Patent Engineering -- The Structure of a Patent -- Inventions and Inventorship : Challenges and Complications -- Patent Engineering and Patent Prosecution -- Controlling the Costs of Generating and Maintaining a Patent Portfolio through Patent Engineering -- Patent Engineering in a Global Economy -- Avoiding an Infringement Lawsuit through Patent Clearances -- The Role of the Patent Engineer.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
John Wiley and Sons
Keywords: Patent laws and legislation -- United States; Patents -- Economic aspects -- United States; LAW -- Intellectual Property -- General; Patent laws and legislation; Patents -- Economic aspects; United States